Concepções de professores de Matemática quanto à utilização de objetos de aprendizagem: um estudo de caso do projeto RIVED-Brasil - Assis, Leila Souto de (2005)
The present study investigates the Mathematics teachers conceptions about the possible uses of learning objects from RIVED-Brazil project as potential aided resources in the Mathematics presential teaching and learning process using computational environments. In order to identify such conceptions, we assumed a qualitative approach through case study, under GODOY (1995) and CHIZZOTTI (2003) perspectives, of RIVED-Brazil project, adopting semi-structured interviews as our data collecting technique based con TRIVIÑOS (1987) perspective. Interested in this reflection, we analyze the current practices of the interviewed teachers, their intentions and ideal expectations about the tools, resources, technologies and environments as well as, after these points of view, we present the two educational modules selected for this research, intending identify which are the possibilities that, for these Mathematics teachers, can immerge from the use of them. Our aim is to study the potential contributions that can occur from the integration among the use of Mathematics learning objects, which belong to the educational modules selected for this research, and the expectations and current teaching practices of the interviewed teachers. In order to do that, three Mathematics teachers were interviewed and two educational modules were selected from RIVED-Brazil project, analyzing all of that under some aspects related to Activity Theory based on ENGESTRÖM (1999) perspective, mainly focusing on the expansive cycle definition